2007
DOI: 10.1291/hypres.30.439
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1 Receptor Blocker Attenuates Myocardial Remodeling and Preserves Diastolic Function in Diabatic Heart

Abstract: Blockade of the renin-angiotensin system reduces cardiovascular morbidity and mortality in diabetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 40 publications
2
44
1
6
Order By: Relevance
“…As expected, CTGF expression, which is known to be angiotensin-II driven, was downregulated to a similar degree by both the QHI and LOS treatment groups, despite the blood pressure difference between these two groups. [34][35][36] The combined DXQ treatment group did not show such effects, showing the angiotensin-II doseinhibition effect. Interestingly, we have found a downregulation of the thioredoxininteracting protein (Txnip) in early LVH but not in late LVH.…”
Section: Proliferation/cell Growthmentioning
confidence: 86%
“…As expected, CTGF expression, which is known to be angiotensin-II driven, was downregulated to a similar degree by both the QHI and LOS treatment groups, despite the blood pressure difference between these two groups. [34][35][36] The combined DXQ treatment group did not show such effects, showing the angiotensin-II doseinhibition effect. Interestingly, we have found a downregulation of the thioredoxininteracting protein (Txnip) in early LVH but not in late LVH.…”
Section: Proliferation/cell Growthmentioning
confidence: 86%
“…However, more markers of specific intracellular AT1R downstream signaling need to be established to support this hypothesis. A recent study by Tsutsui et al (2007) reports on the beneficial effects of the AT1R blocker candesartan on diastolic dysfunction as well as myocardial interstitial fibrosis and TGF-b-CTGF expression in diabetic mice. This study supports our findings on the central role of AngII in mediating the structural and functional abnormalities of the diabetic heart, in addition to the previously described role of increased oxidative stress in diabetic complications in general (Griendling et al 1994) and the diabetic heart in particular (Fiordaliso et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…44 Duisters et al 45 reported that CTGF is regulated by two major cardiac microRNAs, which were downregulated in several models of cardiac hypertrophy and heart failure. Recently, Panek et al 46 reported that cardiomyocyte-specific CTGF transgenic mice developed cardiac dysfunction but did not develop cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%